Photocatalytic chemoselective cleavage of C–O bonds under hydrogen gas- and acid-free conditions. Issue 53 (23rd May 2018) - Imamura, Kazuya; Kato, Hiroko; Wada, Yuichiro; Makabe, Kazuhiro; Onda, Ayumu; Tanaka, Atsuhiro; Kominami, Hiroshi; Sato, Katsutoshi; Nagaoka, Katsutoshi
Abstract : In the presence of a palladium-loaded TiO2 photocatalyst, the cleavage of benzyl phenyl ether derivatives afforded toluenes and phenols simultaneously. Abstract : In the presence of a palladium-loaded TiO2 photocatalyst, the cleavage of benzyl phenyl ether in low-molecular-weight alcohol solvents under de-aerated conditions afforded toluene and phenol simultaneously in a 1 : 1 molar ratio.